2010
DOI: 10.1371/journal.pone.0013143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Esterase Rv0045c from Mycobacterium tuberculosis

Abstract: BackgroundIt was proposed that there are at least 250 enzymes in M. tuberculosis involved in lipid metabolism. Rv0045c was predicted to be a hydrolase by amino acid sequence similarity, although its precise biochemical characterization and function remained to be defined.Methodology/Principal FindingsWe expressed the Rv0045c protein to high levels in E. coli and purified the protein to high purity. We confirmed that the prepared protein was the Rv0045c protein by mass spectrometry analysis. Circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Therefore, it may be hypothesized that Rv1430 like other serine hydrolases is involved in ester metabolism under less favourable conditions in this pathogen. This further supports the hypothesis that M. tuberculosis becomes more pathogenic at alkaline pH as proposed by [34]. From the results of the effect of salt concentration on the enzyme activity of Rv1430 and PE-PPE domain, it may be interpreted that, the secondary structure and ionic interactions related to enzyme activity of the protein is further stabilized in the presence of salt.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, it may be hypothesized that Rv1430 like other serine hydrolases is involved in ester metabolism under less favourable conditions in this pathogen. This further supports the hypothesis that M. tuberculosis becomes more pathogenic at alkaline pH as proposed by [34]. From the results of the effect of salt concentration on the enzyme activity of Rv1430 and PE-PPE domain, it may be interpreted that, the secondary structure and ionic interactions related to enzyme activity of the protein is further stabilized in the presence of salt.…”
Section: Discussionsupporting
confidence: 87%
“…The potential to hydrolyse pNPC4 was almost 50% greater for the domain as compared to full-length protein (Figure 4). Based on the kinetic parameters, our studies show that the preferred substrate of Rv1430 was p -nitrophenyl caproate (C6), similar to that of Rv0045c, a characterized esterase of M. tuberculosis [34]. However, Rv1430 could catalyze C4 and C8 substrates, while Rv0045c showed better activities with C2 and C14.…”
Section: Discussionmentioning
confidence: 85%
“…These genes may be important in establishment of the infection process. Of these genes, g9652 (Table 3) showed high identity to a triacylglycerol lipase gene, a virulence factor gene in Mycobacteria tuberculosis [38, 39]. In pathogenic fungi, it has been suggested that lipases in general are involved in the penetration of the waxy cuticle [40].…”
Section: Discussionmentioning
confidence: 99%
“…Routine enzyme assays were carried out at 50 °C in a 1 mL volume containing 50 mM Tris‐HCl (pH 8.0), 0.5 mM substrate, and 5 μL of the purified enzyme. Enzymatic activity against p ‐nitrophenyl esters was determined by measuring the amount of p ‐nitrophenol released through esterase‐catalyzed hydrolysis . The production of p ‐nitrophenol was continuously monitored at 410 nm with a thermostated Cary 300 UV‐Vis spectrophotometer, California, USA (Varian, Palo Alto, CA, USA) using a molar extinction coefficient of 15,000 M −1 cm −1 .…”
Section: Methodsmentioning
confidence: 99%